Social Entrepreneurship Growth Model among Tanjungpura University Students in Supporting the Smart Village in West Kalimantan Province - M. Irfani Hendri; Hasanudin Hasanudin; Syahbandi Syahbandi (Budapest International Research and Critics University, 2022)
This paper aims to describe the profile of villages in West Kalimantan Province and then design a synergistic model in the growth of solopreneurs in supporting the smart village 4.0 program in West Kalimantan Province. The approach used in this research is a qualitative approach. The type of this research is a case study (case study). The collection of data and information needed for the purposes of analysis is carried out by means of: 1) documentation studies; 2) field observations; 3) interview technique and 4) focus group discussion (FGD). The development of sociopreneurship, especially among the younger generation, is very important considering that Indonesia, including in West Kalimantan Province, has a population with a very high productive age. This population of productive age will certainly have a very good potential if it can be managed and directed to support development programs in West Kalimantan Province, especially the 2031 village development program into smart villages (Desa 4.0) which is the flagship program of the West Kalimantan Provincial Government. The young generation of West Kalimantan, especially students at Tanjungpura University, who are increasingly aware of technology and innovation will spur the progress of renewable resources based industries that are widely available in villages. By utilizing relevant technology, it will spur the emergence of creativity and innovation so that it can become a competitive advantage. Therefore, it would be better to combine sociopreneurship with digital start-ups into one form of subject with the student creativity program (PKM) and the Holistic Village Development and Empowerment Program (PHP2D) as outputs in the lecture.